STUDI TENTANG NILAI-NILAI PANCASILA YANG TERKANDUNG DALAM TRADISI TABUIK DI KELURAHAN PERAK KOTA PARIAMAN - Sari Zulyanisa; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on Tradition Tabuik conducted by community of silver town of Pariaman. The problem formulation in this research is whether there are values of Pancasila in Tabuik tradition in Pariaman silver city. This study aims to determine the values of Pancasila in Tabuik tradition tradition in Kelurahan Perak of Pariaman City. This research was conducted in Kelurahan Perak city of Pariaman in January 2018 until May 2018. This research is descriptive qualitative which become informant in this research is informant chosen purposively as needed and combined with snowbowling technique. The informants studied are as follows: tabuik figures, cultural figures, community leaders, and people Pariaman. Using data collection techniques: Observation, Interview, Documentation Method with triangulation technique. Using the technique of data analyst Techniques: Data collection, reduction, presentation of data, conclusions and verification. Based on the results of research shows that there are values of Pancasila from the five sila namely, divine majesty, just and civilized humanity, Indonesian unity, led by the wisdom wisdom in the deliberation of representation and social justice for all the people of Indonesia.yang contained in tabuik tradition in the urban village of Pariaman silver. Thus the hypothesis that there are Pancasila value contained in tabuik tradition in Kelurahan Perak of the Pariaman City.Keywords: Pancasila Values, Tabuik Tradition of Pariaman Community.